(untitled) (CAHIERS MAGELLANES-NS, 2024)
Tax planning is an essential aspect of financial management for business owners, offering numerous benefits that enhance business growth, sustainability, and profitability. Effective tax planning practices allow businesses to minimize their tax liabilities by leveraging deductions, exemptions, and other tax-saving opportunities provided under the law. By doing so, business owners can optimize cash flow, ensuring that more capital is available for reinvestment and expansion, which is critical for the long-term success of any business. This explores the perception and importance of tax planning practices among business owners. The research aims to evaluate how business owners view tax planning as part of their financial strategies and to examine the relationship between their demographic profiles (age, education, and company turnover) and their approach to tax planning. A sample of 245 business owners from Ahmedabad was analysed, examining their reliance on tax advisors, use of tax-saving instruments, and consideration of tax-saving opportunities in investment decisions. The study reveals that business owners significantly rely on tax advisors and incorporate tax-saving opportunities into their business strategies. Additionally, demographic factors play a crucial role in shaping business owners' perceptions and satisfaction with available tax-saving options. These findings underscore the need for tailored tax planning advisory services for different segments of business owners, contributing to more effective tax management and business growth.